Overview Of Technology In Classroom Assessment From The Perspective Of Students, Educators, And Administrators - Adenigba, Femi John; Onasanya, Samuel Adenubi (Jurnal Pendidikan Ilmu Sosial, 2021)
The application of technological widgets for classroom assessment will have a giant influence on students, educators, and administrators academic success. Entering a proper assessment is critical in developing and creating positive knowledge habits and learning success. Still, academic achievement depends upon close relationships between administrators, educators, and students in the design, development, and operation of technology-predicated assessments. This study, thus, delves into the overview of technology in classroom assessment from the perspective of the classroom and students, instructors, and administrators. The objectives of this study were to examine the perspective of students towards the use of technology for classroom assessment, inquiry the educator's perspective towards the use of technology for classroom assessment, and ascertain the usage of technology in classroom assessment from the perspective of administrators. The study espoused the cross-sectional check approach, using the quantitative exploration design. 175 respondents were the sample used for this study. A disquisition-designed questionnaire was used to gather data for the study. The data analysis fashion used to answer the exploration questions is frequency count and probabilities.